Effect of excavation on performance of adjacent buildings - Halim, Darwid (2008)
Deep excavations in urban area can damage surrounding buildings. The current practice in assessing building damage is based on greenfield settlement computed from 2-D finite element analysis. This is less than satisfactory for situations where 3-D effect is prominent. In this case, a 3-D analysis is preferred. Unfortunately, the 3-D finite element analysis is a fairly complex and demanding task. A simple method has been developed to estimate 3-D settlement from 2-D analysis. The conventional method also assumed that the building would settle the same amount as the ground. This assumption is reasonable for buildings supported on individual footings without ground beams. For frame structures and buildings supported on rafts, the differences in building and ground settlements can be significant. A new method has been developed to integrate the soil-structure interaction into the analysis so that the structure stiffness can be taken into consideration. A new chart for damage assessment of frame structures has also been developed. The chart divides the damage into several categories.